Threats to the Conservation of Asian Elephants: A review study (Journal of Governance and Development (JGD), 2016)
The paper aims to examine the main threats to the conservation of the Asian elephants and identify the factors associated to these threats and their implications for the Asian elephants. We compiled and reviewed journal articles published between 2004 and 2014. We carried out a search using Science Direct, Springer Link, and Gajah. The information obtained was interpreted using thematic content analysis. According to the findings, the main threats to Asian elephants were habitat loss and fragmentation, human-elephant conflict (HEC), poaching and accidents. The rapid conversion of forests into plantations and human-dominated areas, including infrastructure developments, had reduced and fragmentised elephants’ habitat and home range. As a result, elephants caused conflicts in the forms of crop raidings, property damages, human or elephants’ injuries or deaths. The high demand and monetary return from elephant body parts trafficking, particularly ivory, are the main reasons that threatened elephant population. The fragmentation of elephants’ habitat due to conversion of forests into plantations, human-dominated areas and infrastructures developments also increased poachers’ accessibility. Furthermore, the study found that poverty and corruption also contributes to elephant poaching. Besides that, literature also shows that snare injuries, HEC, abandoned mining areas and train movements were causes to accidents that threatened elephants.